2015
DOI: 10.3389/fpsyt.2015.00090
|View full text |Cite
|
Sign up to set email alerts
|

Social and Cultural Elements Associated with Neurocognitive Dysfunctions in Spinocerebellar Ataxia Type 2 Patients

Abstract: Spinocerebellar Ataxia Type 2 (SCA2) is a rare genetic disorder producing cerebellar degeneration and affecting motor abilities. Neuroimaging studies also show neurodegeneration in subcortical and cortical regions related to emotional and social processes. From social neuroscience, it is suggested that motor and social abilities can be influenced by particular cultural dynamics so, culture is fundamental to understand the effect of brain-related alterations. Here, we present the first analysis about the cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 97 publications
0
3
0
Order By: Relevance
“…Cerebellar activation has been reported while Christian practitioners read The Lord's Prayer (Schjoedt et al, 2009) and has classically been associated with motor functions. It is also related to attention and fine affective expressions in social situations (Sacchetti et al, 2002;Mercadillo et al, 2015). Auditory, motor, and sensory functions inferred for this contrast may be necessary not only for believers but also for nonbelievers when analyzing a complex text in abstract terms, as religion requires.…”
Section: Discussionmentioning
confidence: 99%
“…Cerebellar activation has been reported while Christian practitioners read The Lord's Prayer (Schjoedt et al, 2009) and has classically been associated with motor functions. It is also related to attention and fine affective expressions in social situations (Sacchetti et al, 2002;Mercadillo et al, 2015). Auditory, motor, and sensory functions inferred for this contrast may be necessary not only for believers but also for nonbelievers when analyzing a complex text in abstract terms, as religion requires.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the reciprocal connections of the cerebellum with the prefrontal and cingulate cortices point to its relevance for moral cognition ( Demirtas-Tatlidede and Schmahmann, 2013 ). Clinical approaches have reported that cerebellar damage causes alterations in mentalization, empathy, and social cognition ( Gerschcovich et al, 2011 ; Mercadillo et al, 2015b ). The relevance of the cerebellum for compassion may depend on sensory input, and how much it affects higher-order cognition remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…However, activation in the posterior cerebellum has been reported when watching and reading compassion-evoking stimuli in Mexican samples (Mercadillo, Alcauter, et al, 2015;Mercadillo et al, 2011Mercadillo et al, , 2017. Also, the cerebellum has been proposed as an important brain structure to regulate, express, and infer others' emotions through a neural network involving motor and sensorial-related cortical areas (Baumann & Mattingley, 2012;Mercadillo, Galvez, et al, 2015;Stoodley & Schmahmann, 2010). Therefore, we can infer that participants performed an introspective process, and not only a mere resting condition; introspection may not be a passive process, but related to active inner imaginative sensorial and motor processes.…”
Section: Locationmentioning
confidence: 99%